Effective removal of crystal violet from aqueous solution by graphene oxide incorporated hydrogel beads as a novel bio-adsorbent: kinetic, isotherm and thermodynamic studies - Tamer, Yasemin; Berber, Hale (TAYLOR & FRANCIS INC, 2022)
This study revealed the facile preparation of graphene oxide (GO) containing sodium alginate (SA) and hydroxyethyl cellulose (HEC) hydrogel beads that could be used as a low-cost and environmentally friendly bio-adsorbent for the removal of crystal violet (CV). The thermogravimetric analysis (TGA) and absorbency under load (AUL) test results demonstrated that the thermal stability and mechanical strength of SA-HEC hydrogel beads were enhanced by the existence of GO. The SA-HEC/GO bio-adsorbents displayed superior adsorption capability toward cationic CV dye molecules and the adsorption capacity increased from 123.16 mg g(-1) to 312.72 mg g(-1) at pH 5 by incorporation of 1 wt% GO. The CV adsorption is well-described by pseudo-second-order model and was mainly controlled by intra-particle diffusion. Also, the Langmuir and Temkin isotherm models confirmed the physical monolayer adsorption of CV. The calculated thermodynamic parameters such as Gibbs free energy (Delta G degrees), enthalpy (Delta H degrees) and entropy (Delta S degrees) indicated that the adsorption of CV onto SA-HEC/GO bio-adsorbents was spontaneous and it was favored at high temperatures. The bio-adsorbent retained its ability to adsorb CV with a removal efficiency of 79.4% for up to six cycles.
Keywords: Sodium alginate; hydroxyethyl cellulose; graphene oxide; hydrogel beads; cationic dyes; METHYLENE-BLUE; DYE REMOVAL; EFFICIENT ADSORBENT; HEAVY-METAL; ADSORPTION; OPTIMIZATION; COMPOSITE; CHITOSAN; WATER; Polymer Science